Services Trade Restrictiveness Index (STRI): Construction, Architecture and Engineering Services - Geloso Grosso, Massimo (OECD Publishing, 2014)
This paper presents the services trade restrictiveness indices (STRIs) for construction, architecture and engineering services. The STRIs are composite indices taking values between zero and one, zero representing an open market and one a market completely closed to foreign services providers. The indices are calculated for 40 countries, the 34 OECD members and Brazil, China, India, Indonesia, Russia and South Africa. This report presents the first vintage of indicators for construction, architecture and engineering services and captures de jure regulations in force in 2013. The results for construction services indicate that the overall level of restrictiveness is relatively low, ranging from 0.05 to 0.32, with an average of 0.16. The more elevated levels of restriction can be largely attributed to general measures affecting all sectors of the economy. The STRI also supports the view that architecture and engineering services are less restrictively regulated than other accredited professional services, notably legal and accounting services. The average value for the STRI among the countries in the sample is 0.22 for architecture services, connoting a relatively low degree of regulatory restrictiveness; the corresponding value is only marginally lower, 0.2, for engineering services. The majority of regulations affecting trade in these sectors concern the movement of people
Keywords: Trade